2019
DOI: 10.4049/immunohorizons.1800079
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the FOXP1 Transcription Factor Leads to Deregulation of B Lymphocyte Development and Function at Multiple Stages

Abstract: The FOXP1 transcription factor is expressed throughout B cell development until its extinction just prior to terminal differentiation. Foxp1 nulls die of cardiac defects at midgestation, but adult rescue via fetal liver transfer led to a strong pre-B cell block. To circumvent these limitations and to investigate FOXP1 function at later stages of B cell differentiation, we generated and analyzed floxed (F) Foxp1 alleles deleted at pro-B, transitional (T) 1, and mature B cell stages. Mb-1cre-mediated deletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…This strongly indicated that the repressive role of histone or non-histone modification, as well as the more conventional transcriptional repression documented for both SMYD1 and skNAC ( Yahalom et al., 2018 ; Tracy et al., 2018 ; Franklin et al., 2016 ; Murayama et al., 2015 ; Rasmussen et al., 2015 ; Rasmussen and Tucker, 2018 ; Fujii et al., 2016 ; Hsia and Zon, 2005 ), are essential features for future exploration. To comprehensively address this issue, we plan to carry out global transcriptional analyses, including Chip-seq of both human and mouse genomes following SMYD1 and skNAC loss, using approaches we have performed previously for a number of TFs ( Dekker et al., 2016 , 2019 ; Kim et al., 2016b ; Ippolito et al., 2014 ). We also plan to determine the methylation status catalyzed by SMYD1 HMTase activity that may supplement the transcriptional regulation determined here using methods we have employed previously ( Rhee et al., 2014 ; An et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This strongly indicated that the repressive role of histone or non-histone modification, as well as the more conventional transcriptional repression documented for both SMYD1 and skNAC ( Yahalom et al., 2018 ; Tracy et al., 2018 ; Franklin et al., 2016 ; Murayama et al., 2015 ; Rasmussen et al., 2015 ; Rasmussen and Tucker, 2018 ; Fujii et al., 2016 ; Hsia and Zon, 2005 ), are essential features for future exploration. To comprehensively address this issue, we plan to carry out global transcriptional analyses, including Chip-seq of both human and mouse genomes following SMYD1 and skNAC loss, using approaches we have performed previously for a number of TFs ( Dekker et al., 2016 , 2019 ; Kim et al., 2016b ; Ippolito et al., 2014 ). We also plan to determine the methylation status catalyzed by SMYD1 HMTase activity that may supplement the transcriptional regulation determined here using methods we have employed previously ( Rhee et al., 2014 ; An et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Foxp1 deletion in mature B cells also hinders T cell–independent B cell responses, production of IgG3, and B1 cell development ( Patzelt et al, 2018 ). A previous study of T cell–dependent antibody responses showed no clear difference in IgG1 serum titers in B cell lineage–specific Foxp1 -deficient mice ( Dekker et al, 2019 ; Patzelt et al, 2018 ), but this finding is complicated by developmental defects that result in fewer mature B cells in these mice ( Hu et al, 2006 ). Foxp1 -deficient B cells did not show proliferative defects in our system, decoupling the CSR defect in these mice from proliferation.…”
Section: Discussionmentioning
confidence: 88%
“…FoxP1 overexpression represses expression of proapoptotic genes in B cells (34). FasL was identified as one of these proapoptotic genes directly repressed by FoxP1 (35). Transcriptome analysis of a FoxP1-depleted human colon carcinoma cell line showed an upregulation of Forkhead box transcription factor class O (FOXO) target genes that include Fas (36).…”
Section: Discussionmentioning
confidence: 99%